Study of physical-chemical stability in contaminated conditioners by bacteria - Isaac, Vera Lúcia Borges [UNESP]; Ricarte, Patrícia de C.; Magnani, Caroline; Cefali, Leticia C.; Corrêa, Marcos Antônio [UNESP]; Salgado, Herida Regina Nunes (My University, 2013)
This work was carried out accelerated stability study that aims to provide data to predict the stability of the product. Emulsions were analyzed with and without preservatives, deliberately contaminated with Staphylococcus aureus and Pseudomonas aeruginosa and samples with no contaminants. The test formulations were subjected to stress conditions to accelerate the emergence of signs of instability. The conditions used were: heating in oven (45 ± 2 ºC), cooling in the refrigerator (5 ± 2 ºC) and room temperature (22 ± 2 ºC). The samples were evaluated at time zero, 24 hours, 7, 15, 30, 60 and 90. We evaluated the organoleptic characteristics (appearance, color and odor) and the physico-chemical (pH, rheological behavior and density). Based on the results obtained in accelerated stability tests, it was observed that the inoculation of microorganisms do not result in significant changes and did not affect the physico-chemical properties, once the samples did not change, even though all situations in which theoretically would facilitate the process of instability. These results reflect the importance of microbiological control of cosmetic products, once the deliberate contamination of creams did not influence the physical stability of the formulation.
Keywords: Conditioners; Cosmetic products; Microorganisms; Stability test